Civil War places : seeing the conflict through the eyes of its leading historians - Gallagher, Gary W.; Gallman, J. Matthew (James Matthew); Gallagher, Will, 1968- (The University of North Carolina Press, 2019)
Much has been written about place and Civil War memory, but how do we personally remember and commemorate this part of our collective past? How do battlefields and other historic places help us understand our own history? What kinds of places are worth remembering and why? In this collection of essays, some of the most esteemed historians of the Civil War select a single meaningful place related to the war and narrate its significance. Included here are meditations on a wide assortment of places--Devil's Den at Gettysburg, Hollywood Cemetery in Richmond, the statue of William T. Sherman in New York's Central Park, Burnside Bridge at Antietam, the McLean House in Appomattox, and more. Paired with a contemporary photograph commissioned specifically for this book, each essay offers an unusual and accessible glimpse into how historians think about their subjects. In addition to the editors, contributors include Edward L. Ayers, Stephen Berry, William A. Blair, David W. Blight, Peter S. Carmichael, Frances M. Clarke, Catherine Clinton, Stephen Cushman, Stephen D. Engle, Drew Gilpin Faust, Sarah E. Gardner, Judith Giesberg, Lesley J. Gordon, A. Wilson Greene, Caroline E. Janney, Jacqueline Jones, Ari Kelman, James Marten, Carol Reardon, Aaron Sheehan-Dean, Brenda E. Stevenson, Elizabeth R. Varon, and Joan Waugh.